1994
DOI: 10.1103/physrevlett.72.1356
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption on and desorption from Si: Considerations on the applicability of detailed balance

Abstract: The translational energy of Dz desorbed from Si(100) and Si(111) surfaces was measured and found roughly equal to the thermal expectation at the surface temperature T,. Combining these results with previously measured internal state distributions, the total energy of the desorbed molecules is approximately equal to the equilibrium expectation at T,. Thus adsorption experiments, which suggest a large energetic barrier, are at variance with desorption experiments, which exhibit a trivial adsorption barrier, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 36 publications
5
90
3
Order By: Relevance
“…The quite large final translational energies for the desorbing D 2 predicted for both the asymmetric and symmetric paths ͑͗E f ͘ϭ0.45 and 0.63 eV, respectively͒ are in strong qualitative disagreement with the experiment of Kolasinski et al 14 who find ͗E f ͘ϭ0.077Ϯ0.08 eV. Possible rationales for this disagreement are discussed in the next section.…”
Section: B Desorptioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The quite large final translational energies for the desorbing D 2 predicted for both the asymmetric and symmetric paths ͑͗E f ͘ϭ0.45 and 0.63 eV, respectively͒ are in strong qualitative disagreement with the experiment of Kolasinski et al 14 who find ͗E f ͘ϭ0.077Ϯ0.08 eV. Possible rationales for this disagreement are discussed in the next section.…”
Section: B Desorptioncontrasting
confidence: 44%
“…13 Desorbing species were found to be rotationally cold and only weakly vibrationally excited. Recent laser induced thermal desorption experiments also show that desorbing D 2 is translationally equilibrated at the surface temperature, 14 i.e., cold as well. Combining these two experiments implies that the barrier to adsorption should be quite small.…”
Section: Introductionmentioning
confidence: 99%
“…3c). Such a dynamical behavior can to some extent explain the puzzling observations of a very large adsorption barrier in sticking-coefficient measurements [21] and at the same time of a negligible translational energy for the desorbing H2 molecules [22].…”
mentioning
confidence: 99%
“…As for Si(100)-(2 x 1), sticking-coefficient measurements have shown that adsorption is activated with an effective barrier of 0.87 +0.1 eV [21]. Vice versa, time-of-flight measurements have shown no excess translational kinetic energy of desorbing H 2 molecules [22].…”
mentioning
confidence: 99%
“…49 Hydrogen molecules desorbing from Si(100) are vibrationally hot50, 51 but rotationally cold; 50 , 5 1 the angular distribution is peaked toward the surface normal 52 but the velocity distribution is approximately thermal. 53 The available experimental evidence seems to favor a sequential 32 ' 5 1 desorption mechanism between H atoms paired on a single dimer. 42 -4 6 , 4 9 ,51,54 The near-first-order kinetics can be explained by preferential pairing of adsorbed hydrogen, 4 3 "46, 54 which is driven by the nt bond 55 on "unoccupied" surface dimers and has been observed directly by scanning tunneling microscopy (STM).54 Fitting the deviation from first-order kinetics at low coverage to the predictions of our doubly-occupied dimer model 4 3 leads to estimates of 5-7 kcal/mol and = 5 kcal/mol for the pairing energies of hydrogen on Si(100) 43 - 4 5 and Ge(100), 46 which is also a measure of the it bond strength on the clean surface.…”
Section: Introductionmentioning
confidence: 99%